2011
DOI: 10.1002/qj.964
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of atmospheric boundary layer height using ceilometer backscatter data assisted by a boundary layer model

Abstract: This work tackles the problem of the automated detection of the atmospheric boundary layer (BL) height h, from aerosol lidar/ceilometer observations. A new method, the Bayesian selective method (BSM), is presented. It implements a Bayesian statistical inference procedure which combines in a statistically optimal way different sources of information. Firstly, atmospheric stratification boundaries are located from discontinuities in the ceilometer backscattered signal. The BSM then identifies the discontinuity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…8) in order to prevent the detection of RL signals or lofted aerosol layers. Other methods to prevent the incorrect detection of the BLH include those proposed by de Haij et al (2006), Di Giuseppe et al (2012, and Pal et al (2013). However, our study uses the height restraint as it has been shown to successfully prevent the detection of RL signals in the example shown in Fig.…”
Section: Wavelet Methods Resultsmentioning
confidence: 97%
“…8) in order to prevent the detection of RL signals or lofted aerosol layers. Other methods to prevent the incorrect detection of the BLH include those proposed by de Haij et al (2006), Di Giuseppe et al (2012, and Pal et al (2013). However, our study uses the height restraint as it has been shown to successfully prevent the detection of RL signals in the example shown in Fig.…”
Section: Wavelet Methods Resultsmentioning
confidence: 97%
“…It is also worth mentioning the method proposed in Steyn et al (1999), which consists of fitting an idealized backscatter profile at the transition between the BL and the FT. In the more recent literature there are examples of different methods combining the lidar gradient-based retrievals with temporal height-tracking techniques, for example observational (Martucci et al, 2010a, b), predictive (Tomás et al, 2010) or model-based first guesses (Di Giuseppe et al, 2012). Pal et al (2013) proposed a simplified bulk model combined with surface turbulence measurements and atmospheric variance measurements, to help select the BL height amongst all candidates.…”
Section: Overview Of Existing Algorithmsmentioning
confidence: 99%
“…The data obtained with a SO 2 monitor (model 43i-TLE, Thermo Scientific) were also utilized. Furthermore, the measurement station was equipped with a ceilometer (Jenoptik CHM15K), which allowed us to monitor the evolution of planetary boundary layer (PBL; Di Giuseppe et al, 2012;Angelini and Gobbi, 2014).…”
Section: Site Description and Instrumentationmentioning
confidence: 99%